A new perspective: Establishing developmental profiles of premature infants based on Bayley-III scores at age 2. Issue 2 (3rd April 2022) - Kenyhercz, Flóra; Nagy, Beáta Erika
Abstract: Longitudinal and cross-sectional studies in early childhood generally focus on different developmental areas separately. The aim of this study is to identify the most common developmental profiles regarding cognitive, language and motor skills among low birthweight (LBW) children. Our sample included 208 LBW children examined at 24–28 months. We used cluster analysis to identify developmental profiles based on the scores of the Bayley-III Cognitive, Language and Motor scales. We found three consistent profiles (High, Mildly Delayed and Severely Delayed) and three inconsistent, average profiles (with High Expressive Language, with Mildly Delayed Expressive Language and with Severely Delayed Language). Socioeconomic status, maternal education, in vitro fertilization, plurality and chronic morbidities were significantly related to the clusters. Cluster analysis might be an effective method to identify developmental profiles of preterm (and other at-risk) children, which might result in a more complex understanding of cognitive and psychomotor development in early childhood.